2019
DOI: 10.1111/epi.16297
|View full text |Cite
|
Sign up to set email alerts
|

Dravet syndrome: Early electroclinical findings and long‐term outcome in adolescents and adults

Abstract: To describe the outcome of Dravet syndrome (DS) in adolescents and adults we conducted a longitudinal retrospective study of two independent cohorts of 34 adolescents (group 1) and 50 adults (group 2). In both cohorts, we collected information about genetic mutation, and semiology of seizures at onset and during disease course.At the last evaluation, we considered the following features: epilepsy (distinguishing myoclonic/complete and nonmyoclonic/incomplete phenotype), neurologic signs, intellectual disabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 40 publications
(97 reference statements)
5
46
1
Order By: Relevance
“…Because there was no statistically signi cant difference between language, ambulation or seizure characteristics for those with and without vaccine-related seizures, the vaccination should not be withheld in patient with DS, and all clinicians should provide families with proper information before administering vaccination. In previous literatures, seizure frequency may decrease with age, which was independent of their SCN1A mutation type [12][13][14][15]. We also found a tendency of decreasing seizure frequency with age, although this did not reach statistical signi cance.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…Because there was no statistically signi cant difference between language, ambulation or seizure characteristics for those with and without vaccine-related seizures, the vaccination should not be withheld in patient with DS, and all clinicians should provide families with proper information before administering vaccination. In previous literatures, seizure frequency may decrease with age, which was independent of their SCN1A mutation type [12][13][14][15]. We also found a tendency of decreasing seizure frequency with age, although this did not reach statistical signi cance.…”
Section: Discussioncontrasting
confidence: 42%
“…We also found a tendency of decreasing seizure frequency with age, although this did not reach statistical signi cance. In other study, in adolescence and adult groups with DS, fever sensitivity persisted but had less in uence [14].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In 2019, a study conducted by Darra et al showed 70.5 % of 22 adolescents with "complete forms" (i.e., myoclonic phenotype) had moderate or severe ID, whereas the same level of ID was seen in more than 80 % of the 35 adults with the complete phenotype. They also noted that the most cognitive impairment was observed in DS adults with the most persisting seizures [67].…”
Section: Cognitive Behaviour and Social Outcomesmentioning
confidence: 96%
“…Several additional features are frequently reported: eating and sleep disorders, gait deterioration, dysautonomia, and a higher predisposition to infections [9][10][11]. The long-term outcome of individuals with Dravet syndrome remains poor [12][13][14][15]. This syndrome is considered as the archetype of developmental and epileptic encephalopathy (DEE) [16].…”
Section: Introductionmentioning
confidence: 99%